Chulacaridae, a new family of prostigmatic mites (Acari, Trombidiformes) from Thailand - Fuangarworn, Marut; Lekprayoon, Chariya; Butcher, Buntika Areekul (Zootaxa, 2016)
A new family of prostigmatic mites (Acari: Trombidiformes), Chulacaridae n. fam. based on Chulacarus elegans n. g. et n. sp., is described from adult females and immature instars collected from soil and litter in Thailand. The new family is monobasic and is placed in the hyporder Anystae (sensu Zhang et al. 2011), and tentatively grouped with other families in the superfamily Anystoidea. In addition to the typical features of Anystina, Chulacaridae n. fam. is characterized by the presence of enlarged, raptorial legs I uniquely with bipectinate setae on their anterior face, the presence of thick and blunt adoral setae (or1 and or2), the fusion of the palpal femur and genu, the absence of any femoral subdivision of legs I–IV, the presence of 8–10 pairs of small genital papillae, and the presence of unipectinate claws (without empodium) on pretarsi I and normal claws (with claw-like empodium) on pretarsi II–IV. Some morphological characters and its systematic position are discussed.